Year in Review: United Nations Peace Operations, 2010 - United Nations (United Nations, 2012)
The Year in Review features the activities of the UN Peacekeeping Missions in 2010, highlighting the successes and challenges that emerge throughout the year towards maintaining peace and security, protecting civilians, and providing support to fragile societies and governments in a post-conflict setting.